Second Permanent Molar Extraction and Late Lower Arch Crowding: A Ten-Year Longitudinal Study - Richardson Margaret E. (Sciendo, 1996)
The purpose of this investigation was to examine lower arch alignment in the long term following treatment by second molar extraction. Thirty subjects, treated by extraction of four second permanent molars at an average age of 13.9 years, were examined five and ten years after extractions. None had any mechanical treatment in the lower arch. Twenty had some simple upper arch treatment, including, in five cases, extraction of first premolars. The changes in lower arch alignment were measured on study models. There was a small average decrease in lower arch crowding in the first five years following extraction, and little or no change in alignment in the next five years.